Study of Cosmic Radiation Near the Earth's North Geomagnetic Pole. - Pomerantz,Martin A. (1975)
The report discusses cosmic ray intensity observations at AFCRL geopole station and analyzes cosmic ray intensity variations, covering modulations and anisotropies, solar cosmic rays, long term relationships between solar activity and cosmic ray phenomena, and neutron multiplicity studies.